Pls see the above question and help as soon as possible....plss
Attachments:
![](https://hi-static.z-dn.net/files/d8c/aee8ec0a82a61ce7d1a26c1de50d9542.jpg)
Answers
Answered by
1
Answer:
here is ur answer
Step-by-step explanation:
Correction in Question : other wise LHS = 2
(x⁻¹ + y⁻¹)/x⁻¹ + (x⁻¹ - y⁻¹)/y⁻¹ = (x² + y²)/xy
LHS
= (x⁻¹ + y⁻¹)/x⁻¹ + (x⁻¹ - y⁻¹)/y⁻¹
= (1/x + 1/y)/(1/x) + (1/x - 1/y)/(1/y)
= x(y + x) /xy + y(y - x)/xy
= (1/xy) ( xy + x² + y² - yx)
= (1/xy) ( x² + y²)
= (x² + y²)/xy
= RHS
QED
Hence Proved
(x⁻¹ + y⁻¹)/x⁻¹ + (x⁻¹ - y⁻¹)/y⁻¹ = (x² + y²)/xy
HOPE IT HELPS YOU PLZZ MARK IT AS BRAINLIEST ANSWER AND FOLLOW ME
Answered by
1
Answer:
Step-by-step explanation:
Attachments:
![](https://hi-static.z-dn.net/files/dc1/736c77e75a20b1455c5cd2fa57889426.jpg)
Similar questions
Social Sciences,
6 months ago
Biology,
6 months ago
Math,
6 months ago
Computer Science,
1 year ago
Math,
1 year ago
Biology,
1 year ago
Biology,
1 year ago